Kaili sour soup in alleviation of hepatic steatosis in rats via lycopene route: an experimental study - Li, Yi; Cong, Shuo; Chen, Rui; Tang, Juan; Zhai, Liqiong; Liu, Yongmei (Annals of medicine (Helsinki), 2025)
Nonalcoholic fatty liver disease (NAFLD) is one of the most prevalent chronic liver diseases, with a range of manifestations, such as hepatic steatosis. Our previous study showed that Kaili Sour Soup (KSS) significantly attenuated hepatic steatosis in rats. This study explored the main components of KSS and the mechanisms by which it exerts its protective effects against NAFLD. Twenty-four 6-week-old male Sprague-Dowley (SD) rats were randomly assigned to three treatments: feeding a normal standard diet, a high-fat diet, or a high-fat diet plus gavage KSS. The effects of KSS treatment on hepatic lipid accumulation were assessed using biochemical, histological, and molecular experiments. The amounts of KSS ingredients were measured using biochemical assays. Network pharmacology analyses were performed to identify the hub genes of KSS targets and enriched pathways. CCK-8 assay was used to determine the effect of free fatty acids (FFA), lycopene, and estrogen on HepG2 viability. Quantitative Real-Time polymerase chain reaction (qRT-PCR) and Western blot assays were performed to determine the effect of KSS or lycopene on estrogen signaling and expression of lipid metabolism-related molecules. Statistical analyses were performed using GraphPad Prism and SPSS. KSS alleviated fat deposition in rat liver tissue and affected the expression of hepatic lipid synthesis, catabolism, and oxidative molecules. Lycopene was identified as the ingredient with the highest amount in KSS. Network pharmacology analyses showed that the hub genes were enriched in the estrogen signaling pathway. Cellular experiments showed that lycopene increased the expression of Estrogen Receptor α (ERα), Carnitine palmitoyltransferase 1 A ( ), Peroxisome proliferator-activated receptor α ( ) (all < 0.01), and Hormone sensitive lipase ( ) ( < 0.05), and reduced the expression of lipid metabolism-related factors ) ( < 0.01), Acetyl-CoA carboxylase 1 ( ) and Lipoprotein lipase ( ) (all < 0.05). KSS ameliorated abnormal lipid metabolism in patients with NAFLD. Lycopene was the major component of KSS, and it affected estrogen signaling and the expression of lipid metabolism molecules. In short, both KSS and LYC could change lipid metabolism by lowering lipid accumulation and raising lipolysis.